AN ANALYSIS OF LANGUAGE STYLE IN DIALOGUE WITH JACK MA, ALIBABA GROUP, KIEF 2019 - Hermanus Tanggung; I Gusti Bagus Wahyu Nugraha Putra; I Komang Sulatra (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
The aim of this study is to analyse the language style used by Jack Ma in the video “Dialogue with Jack Ma, Alibaba Group, Kief 2019”. This research is conducted by applying the theory five types of language style proposed by Joos (1967). The data were taken from the conversation between Nik Gowing as the host, Jack Ma as the guest and audience business in Ukraine. This research used qualitative method in analysing the data. This study found three types of language style used in dialogue Jack Ma, Alibaba group. The study found formal style, consultative style and casual style on this research. Formal style is used dominantly found in the dialogue. The use of formal style by a word of choice, situation and condition, participant and place. In this style the researcher found six data, while in the casual style, the researcher found five data, for the consultative style, the researcher found five data used by Jack Ma in the video” Dialogue with Jack Ma, Alibaba Group, Kief 2019.